Peran Guru Sejarah untuk Menanamkan Sikap Nasionalisme di Era Globalisasi - Husen Waedoloh; Hieronymus Purwanta; Suryo Ediyono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The role of the teacher is very important in shaping the character of students who have a sense of nationalism. The feeling of nationalism is something that must be held by everyone, especially by students, so that in the process of development it becomes an important capital in the survival of the nation and the state. This paper seeks to obtain information about the participation of history teachers in instilling students' nationalism. The results show that history teachers are very important in instilling an attitude of nationalism in students because the teacher is an example, the teacher is an inspiration, the teacher is a motivator, and the teacher is an evaluator. In learning history itself, the modeling of the character of nationalism is mainly discussed. The method used in this research is the study of literature or library research and by conducting observational studies from previous studies. Library research, Researchers study and collect data through several kinds of literature and reading sources that support and are relevant to research. In this case, literature research is carried out through books, magazines,  internet.